(untitled) (Texas Journal of Engineering and Technology, 2025)
Fused Deposition Modeling (FDM) has gained significant popularity in industrial manufacturing due to its cost-effectiveness, material diversity, and ease of implementation. Unlike other additive manufacturing technologies, FDM enables the creation of complex geometric shapes using various thermoplastic materials, including PLA, PETG, ABS, and advanced composites. This paper examines the industrial applications of FDM, focusing on the physical and chemical properties of these materials, the technical challenges associated with FDM, and the economic feasibility of implementing this technology in mass production. The FDM process operates by extruding thermoplastic filaments layer by layer, forming a solid structure. The final part’s properties depend on factors such as material composition, extrusion temperature, layer adhesion, and print speed. For example, PLA is widely used due to its biodegradability and ease of printing but lacks sufficient mechanical strength for industrial applications. PETG offers better impact resistance and chemical durability, making it suitable for functional parts exposed to environmental stress. ABS is known for its high strength and heat resistance, making it a common choice in the automotive and consumer electronics industries. More advanced materials, such as carbon fiber and polyamide composites, further enhance mechanical properties while reducing weight, making them ideal for aerospace and load-bearing structures